Kemitraan Pemerintah dan Swasta (Public Private Partnership) Pada Pembangunan Drainase di Kecamatan Sunggal - Parulian, Juan Cavin; Afifah, Nur (Universitas Pahlawan Tuanku Tambusai, 2024)
Infrastructure development is an important activity in the development of a country or region. Researchers use the implementation of the Van Mater and Van Horn model in 1975. The qualitative approach uses descriptive research with data collection techniques, namely interviews, observations and documentation. Determination of informants is done by purposive sampling. Data collection in the writing of the study is done primarily and secondary. The results of the study of the size and objective indicators of the policy indicate that the development of Sunggal drainage can be said to have not been achieved optimally. The resource indicator shows that the APBD is the main source of development. The implementing agent characteristic indicator shows that the results of the drainage project seem haphazard. The attitude or tendency indicator of the implementer shows that the drainage development carried out is 'top down'. The inter-organizational communication indicator and the activities of the implementer show that the communication between the government and the private sector is running well, but between the government and the community and the private sector and the community is not running well. The economic, social and political environment indicator shows that the construction of drainage activities is a significant disturbance for the local community